2013
DOI: 10.18869/acadpub.jhs.1.2.28
|View full text |Cite
|
Sign up to set email alerts
|

Structural Quality and Utilization of Outpatient Curative Care Under Family Medicine Scheme in Rural Area of Mazandaran– Iran

Abstract: Background and purpose: Since 2005, a reform known as Rural Insurance and Family Medicine Scheme has introduced to primary health care network in Iran in rural areas and small towns. The content of the reform implies a substantial change in those aspects of health centers that mainly could be categorized as structural quality. Although, this is the requirement of all health care providers, they are not identical in those items. In this article, we have tried to report the relation between structural quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…According to the Aday and Andersen model for access and utilization of care, multiple factors may influence utilization of health services. Such factors may include characteristics of the population at risk and characteristics of the healthcare delivery system (12)(13)(14)(15)(16)). An effective referral system ensures a close relationship between all levels of the health system and helps to ensure people receive the best possible care closest to home.…”
Section: Communication and Transportation Barriers (5)mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Aday and Andersen model for access and utilization of care, multiple factors may influence utilization of health services. Such factors may include characteristics of the population at risk and characteristics of the healthcare delivery system (12)(13)(14)(15)(16)). An effective referral system ensures a close relationship between all levels of the health system and helps to ensure people receive the best possible care closest to home.…”
Section: Communication and Transportation Barriers (5)mentioning
confidence: 99%
“…In many developing countries, a high proportion of clients seen at the outpatient clinics at secondary facilities could be appropriately looked after at primary healthcare centers at lower overall cost to the client and the health system. The design and functioning of a referral system in any individual country will be influenced by many factors such as capabilities of lower levels, availability of specialized personnel, training capacity, organizational arrangements, cultural issues, political issues, traditions, population size, and density, terrain and distances between urban centers, pattern and burden of disease, and demand for and ability to pay for referral care as either health systems determinants or general determinants (13)(14)(15)(16)(17). The aim of this research was then to investigate socio-economic and health seeking behavior of caretakers at using hospital services in Iran.…”
Section: Communication and Transportation Barriers (5)mentioning
confidence: 99%
“…In a national study called ‘Health Services Utilization in Iran’ in 2003, results showed that still 6.4% of the households had not met their services need 11. Underutilisation of primary healthcare in Iran, as a matter of low quality and responsiveness of services, must be an important concern of policy-makers 21…”
Section: Introductionmentioning
confidence: 99%